2003
DOI: 10.1002/chin.200318284
|View full text |Cite
|
Sign up to set email alerts
|

Norbornadiene—Quadricyclane as an Abiotic System for the Storage of Solar Energy

Abstract: Applied chemistryApplied chemistry Z 0300 Norbornadiene-Quadricyclane as an Abiotic System for the Storage of Solar Energy -[112 refs.]. -(DUBONOSOV, A. D.; BREN, V. A.; CHERNOIVANOV, V. A.; Russ. Chem. Rev. (Engl. Transl.) 71 (2002) 11, 917-927; Inst. Phys. Org. Chem., Rostov State Univ., Rostov-on-Don 344090, Russia; Eng.) -Lindner 18-284

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 1 publication
0
27
0
Order By: Relevance
“… 17 19 Both experimental and theoretical aspects of this research field have been reviewed recently. 6 , 18 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“… 17 19 Both experimental and theoretical aspects of this research field have been reviewed recently. 6 , 18 , 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…The bromine atoms account for more than 25% of the total electrons of the system. If the norbornadienes 8 and 9 are to be studied using ultrafast X-ray scattering techniques, it must first be shown that the norbornadienes 8 and 9 can undergo photolytic isomerisation to the corresponding quadricyclanes 8q and 9q As triplet states are involved in the transformation [7][8][9][10][11][12], the bromine atoms might make the process slow or prevent it from happening. Two photolysis experiments are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, potential candidates for the study of transients in a 2 + 2 cycloaddition reaction with time-resolved X-ray scattering studies in solution and the gas phase are presented. The norbornadiene-quadricyclane system has been investigated as a potential system for solar energy storage [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different molecular modifications have been explored to optimize the performance, including the introduction of electron donor and acceptor groups on one or both double bonds. 27 , 29 , 30 , 33 , 34 …”
mentioning
confidence: 99%
“…The presented NBD derivative has already many advantages compared to those of previously reported systems, such as the ease of synthesis 34 and the demonstrated robustness over many cycles. 37 Moreover, NBDs synthesis and physical and chemical behaviors and properties are widely studied and quite well understood, 29 , 32 , 35 , 36 , 38 implying the facilitation of carefully designing molecular systems with the desired properties and predictable physicochemical behavior. Some limitations and challenges can be identified.…”
mentioning
confidence: 99%